Long-term Hearing Preservation and Speech Perception Performance Outcomes With the Slim Modiolar Electrode. Issue 10 (December 2021) - Shew, Matthew A.; Walia, Amit; Durakovic, Nedim; Valenzuela, Carla; Wick, Cameron C.; McJunkin, Jonathan L.; Buchman, Craig A.; Herzog, Jacques A.
Abstract : Objective: Describe audiologic outcomes in hearing preservation (HP) cochlear implant candidates using a slim modiolar electrode (SME). Study Design: Retrospective. Setting: Tertiary referral center. Patients: Two hundred three adult cochlear implant patients with preoperative low-frequency pure-tone average (LFPTA) ⩽ 80 dB HL that received the SME. Intervention: Implantation with a SME electrode. Main Outcome Measures: Primary outcome was postoperative HP, defined as LFPTA ⩽80 dB HL. HP status was analyzed at "early" (activation or 3 mo) and "long-term" (6 or 12 mo) time frames using the patient's worst audiogram. Speech perception tests were compared between HP and non-HP cohorts. Results: Of the 203 HP candidates, the tip fold-over rate was 7.4%. The mean shifts in LFPTA at the "early" and "long-term" time points were 25.9 ± 16.2 dB HL and 29.6 ± 16.9 dB HL, respectively. Of 117 patients with preoperative LFPTA ⩽60 dB HL, the early and long-term mean LFPTA shifts were 19.5 ± 12.3 dB HL and 32.6 ± 17.2 dB HL, respectively; early and long-term HP rates were 61.1% and 50.8%, respectively. For patients with preoperative LFPTA ⩽80 dB HL, early and long-term HP rates were 45.5% and 43.7%, respectively. No significant difference was observed in postoperative speech perception performance (CNC, AzBio, HINT) at 3, 6, or 12 months between HP versus non-HP groups. Conclusions: HP is feasible using the SME. While electroacoustic stimulation was not studied in this cohort, HP provided no clear advantage in speech perception abilities in this group of patients. The current reporting standard of what constitutes HP candidacy (preoperative LFPTA ⩽80 dB HL) should be reconsidered.